The signal transducer CD24 suppresses the germ cell program and promotes an ectodermal rather than mesodermal cell fate in embryonal carcinomas. Issue 4 (2nd August 2021) - Skowron, Margaretha A.; Becker, Teresa K.; Kurz, Lukas; Jostes, Sina; Bremmer, Felix; Fronhoffs, Florian; Funke, Kai; Wakileh, Gamal A.; Müller, Melanie R.; Burmeister, Aaron; Lenz, Thomas; Stefanski, Anja; et al.
Abstract : Testicular germ cell tumors (GCTs) are stratified into seminomas and nonseminomas. Seminomas share many histological and molecular features with primordial germ cells, whereas the nonseminoma stem cell population—embryonal carcinoma (EC)—is pluripotent and thus able to differentiate into cells of all three germ layers (teratomas). Furthermore, ECs are capable of differentiating into extra‐embryonic lineages (yolk sac tumors, choriocarcinomas). In this study, we deciphered the molecular and (epi)genetic mechanisms regulating expression of CD24, a highly glycosylated signaling molecule upregulated in many cancers. CD24 is overexpressed in ECs compared with other GCT entities and can be associated with an undifferentiated pluripotent cell fate. We demonstrate that CD24 can be transactivated by the pluripotency factor SOX2, which binds in proximity to the CD24 promoter. In GCTs, CD24 expression is controlled by epigenetic mechanisms, that is, histone acetylation, since CD24 can be induced by the application histone deacetylase inhibitors. Vice versa, CD24 expression is downregulated upon inhibition of histone methyltransferases, E3 ubiquitin ligases, or bromodomain (BRD) proteins. Additionally, three‐dimensional (3D) co‐cultivation of EC cells with microenvironmental cells, such as fibroblasts, and endothelial or immune cells, reduced CD24 expression, suggesting that crosstalk with the somatic microenvironment influences CD24 expression. In a CRISPR/Cas9 deficiency model, we demonstrate that CD24 fulfills a bivalent role in differentiation via regulation of homeobox, and phospho‐ and glycoproteins; that is, it is involved in suppressing the germ cell/spermatogenesis program and mesodermal/endodermal differentiation, while poising the cells for ectodermal differentiation. Finally, blocking CD24 by a monoclonal antibody enhanced sensitivity toward cisplatin in EC cells, including cisplatin‐resistant subclones, highlighting CD24 as a putative target in combination with cisplatin. Abstract : This study presents the (epi)genetic mechanisms regulating the expression of the signaling transducer CD24 in embryonal carcinoma (EC), a germ cell tumor subtype with embryonic stem cell‐like features. We demonstrated that CD24 expression can be transactivated by the pluripotency factor SOX2 and is involved in suppressing the germ cell program during formation of ECs, while promoting ectodermal differentiation.